Discovery of Novel Cinchona‐Alkaloid‐Inspired Oxazatwistane Autophagy Inhibitors. Issue 8 (18th January 2017) - Laraia, Luca; Ohsawa, Kosuke; Konstantinidis, Georgios; Robke, Lucas; Wu, Yao‐Wen; Kumar, Kamal; Waldmann, Herbert
Abstract: The cinchona alkaloids are a privileged class of natural products and are endowed with diverse bioactivities. However, for compounds with the closely‐related oxazatricyclo[4.4.0.0]decane ("oxazatwistane") scaffold, which are accessible from cinchonidine and quinidine by means of ring distortion and modification, biological activity has not been identified. We report the synthesis of an oxazatwistane compound collection through employing state‐of‐the‐art C−H functionalization, and metal‐catalyzed cross‐coupling reactions as key late diversity‐generating steps. Exploration of oxazatwistane bioactivity in phenotypic assays monitoring different cellular processes revealed a novel class of autophagy inhibitors termed oxautins, which, in contrast to the guiding natural products, selectively inhibit autophagy by inhibiting both autophagosome biogenesis and autophagosome maturation. Abstract : Inhibitors with a twist : Synthesis of a cinchona‐alkaloid‐inspired collection of small molecules through ring‐distortion and further modification of the natural products delivered the novel oxazatwistanes. Unlike the guiding cinchona alkaloids, these compounds inhibit autophagy with an unprecedented mode of action.